2007
DOI: 10.1093/cercor/bhm152
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Spontaneous Activity in the Piriform Cortex

Abstract: Slow spontaneous rhythmic activity is generated and propagates in neocortical slices when bathed in an artificial cerebrospinal fluid with ionic concentrations similar to the ones in vivo. This activity is extraordinarily similar to the activation of the cortex in physiological conditions (e.g., slow-wave sleep), thus representing a unique in vitro model to understand how cortical networks maintain and control ongoing activity. Here we have characterized the activity generated in the olfactory or piriform cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 58 publications
3
25
2
Order By: Relevance
“…Such preferred states are particularly evident in the bimodal distribution of MUA during time in logarithmic scale in Fig. 3c, usually observed in Up/Down slow oscillations experiments (Sanchez-Vives et al 2008;Sanchez-Vives et al 2010;Reig et al 2010).…”
Section: Evidence Of Attractor Dynamics During Slow Up/down Oscillationsmentioning
confidence: 61%
See 1 more Smart Citation
“…Such preferred states are particularly evident in the bimodal distribution of MUA during time in logarithmic scale in Fig. 3c, usually observed in Up/Down slow oscillations experiments (Sanchez-Vives et al 2008;Sanchez-Vives et al 2010;Reig et al 2010).…”
Section: Evidence Of Attractor Dynamics During Slow Up/down Oscillationsmentioning
confidence: 61%
“…1d, e is obtained, the residence times in one of the two preferred states (Up or Down) have approximately an exponential distribution (Gigante et al 2007;Martí et al 2008;Mejias et al 2010), in analogy to the problem of the diffusion over a barrier (Risken 1989). On the other hand, slow oscillation in vitro are quite regular with a relatively low coefficient of variation (Sanchez-Vives and McCormick 2000; Sanchez-Vives et al 2008;Sanchez-Vives et al 2010;Reig et al 2010), as shown in Fig. 3d for an example recording.…”
Section: In Vitro Experiments and Data Analysismentioning
confidence: 99%
“…This could be unexpected since axonal conduction is known to increase with temperature (5%/deg) (Hodgkin and Katz 1949;Johnson and Olsen 1960). However, propagation of activity in the cortical network also depends on other factors such as excitatory/inhibitory balance, reverberation in the network, and excitability of the network (Compte et al 2003;Pinto et al 2005;Sanchez-Vives et al 2008). The larger excitability of neurons in the lower range of temperatures (Volgushev et al 2000b) and their closeness to threshold probably could compensate factors like the slower axonal conduction at cooler temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The pEN, also called area tempestas, is a highly epileptogenic locus (16,17). However, the physiological role of its dense connectivity is unknown (15,18).To probe excitatory connectivity in the olfactory cortex, we isolated excitatory synaptic activity in a tailored brain slice containing the ventral anterior piriform cortex (APC V ), the pEN, the anterior olfactory cortex (AOC; also called anterior olfactory nucleus). Using weak stimulation of the lateral olfactory tract (LOT) input while blocking GABAergic inhibition and NMDA receptors, we evoked transient, all-or-none, network-wide bursts of excitation.…”
mentioning
confidence: 99%
“…The pEN, also called area tempestas, is a highly epileptogenic locus (16,17). However, the physiological role of its dense connectivity is unknown (15,18).…”
mentioning
confidence: 99%